Geotechnical Perspective on Dozer-Push Method in Coal Mining Operations - Dwinagara, Barlian; Hariyanto, Raden; Lusantono, Oktarian Wisnu; Prabandaru, Prasodo Datu (RSF Conference Series: Engineering and Technology, 2022)
The rapid increase of technological development is currently playing a role in the mining industry. The dozer push exploitation method is an alternative to the conventional truck and shovel method. Heavy dozers have the ability to move large amounts of waste material in short distances at a low cost, while trucks and shovels will be more economical if over long distances. Geotechnical assessment becomes one of the critical considerations in making a decision plan and slope design for mining activities where the dozer push activities were carried out. Material conditions greatly affect slope stability, which can be defined as material behavior based on the physical and mechanical properties of the material. The slope stability analysis method used in this study was a combination of two methods, the Limit Equilibrium Method (LEM) and Finite Element Method (FEM). These two combinations of analytical methods will strengthen the justification of the geotechnical perspective. By understanding the behavior of the material on a slope, the risk of a slope failure can be controlled and minimized using a geotechnical perspective. The parameters that will be studied in this study are the physical and mechanical properties of the material against several conceptual design options